DAMPAK PANDEMI COVID-19 TERHADAP KUALITAS PELAYANAN TERAPI WICARA, MOTIVASI KEHADIRAN DAN TINGKAT KEPUASAN PASIEN DI JAWA TENGAH: THE IMPACT OF THE COVID-19 PANDEMIC ON THE QUALITY OF SPEECH THERAPY SERVICES, ATTENDANCE MOTIVATION, AND PATIENT SATISFACTION LEVEL IN CENTRAL JAVA - Sutanto, Alfiani Vivi; Nurhidayah, Lia Ratih (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
COVID-19 has created unprecedented challenges in society with regard to the safety of healthcare personnel and the jeopardizing of the public health system. This can happen if healthcare facilities do not increase their vigilance in protecting healthcare workers. This study is a quantitative, observational and analytical study of 200 people in Central Java. The data analysis used was path analysis, and it was found that the quality of speech therapy services increased (b = 2.58 units; 95% CI = 1.90 to 3.27; p < 0.001), and the level of satisfaction of speech therapy patients increased (b = 1.28 units; 95% CI = 0.61 to 1.95; p < 0.001). In contrast, therapeutic motivation decreased (b = 0.63; 95% CI = 1.21 to -0.05; p=0.033). The conclusion of this study is an increase in service quality, therapeutic motivation and patient satisfaction in speech therapy indirectly influenced by quality and motivation theory.